Marketing Mix Strategy in Islamic Economic Perspective on BSI Gold Pawn Products (Case Study of Bank Syariah Indonesia Kcp Kisaran) - Yulita Astri; Muhammad Lathief Ilhamy Nasution; Tuti Anggraini (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study aims to determine the Marketing Mix Strategy in an Islamic Economic Perspective on Gold Pawn Products (Case Study of Bank Syariah Indonesia KCP Kisaran). Data sources are obtained from primary data, namely through observation, and interviews. While secondary data were obtained from related reading books and documents related to this study. The population of this study is all employees of BSI KCP Kisaran and the sample in this study is the Pawwing Aprraisal staff. From the results of this study, it shows that the products at BSI KCP Kisaran consist of fund distribution and fund raising products. BSI KCP Kisaran Gold Pawn Product Marketing Mix Strategy is using 4P (Product, Price, Promotion, Place). The factors for fluctuations in gold pawn product customers at Bank Syariah Indonesia KCP Kisaran are due to the choice of the customer himself who prefers other products compared to gold installment pawn products. And the marketing mix strategy in the perspective of Islamic economics on BSI Gold Pawn products (Case Study of Bank Syariah Indonesia KCP Kisaran) must be based on God, Ethical, Realistic and Humanist.